PREFERENSI MASYARAKAT DALAM PEMILIHAN MODA TRANSPORTASI PUBLIK DI KOTA YOGYAKARTA - Dwi Kunto Nurkukuh; Amithya Irma Kurniawati (KURVATEK, 2021)
Public interest in public transportation in Yogyakarta City has decreased. This condition is exacerbated by the competition between conventional public transportation and online public transportation. The purpose of this study was to determine people's preferences in choosing the mode of public transportation in Yogyakarta City. The research was conducted using the Analytical Hierarchy Process (AHP). The people of Yogyakarta City pay attention to the mode selection criteria in the following order: 1) Safety, 2) Comfort, 3) Convenience, 4) Time, 5) Cost. The mode of public transportation chosen by the people of Yogyakarta City takes into account these five criteria, namely: 1) Online Car Ojek, 2) Online Motorbike Ojek, 3) Trans Bus, 4) Conventional Taxis, 5) Offline Motorbike Ojek, 6) Pedicab. From the cost criteria, Trans Bus is the most economical. From the time criteria, online motorcycle taxis are the fastest. From the criteria of convenience, online motorcycle taxi is the easiest. From the safety criteria, Online Car Ojek is the safest. From the comfort criteria, Online Car Ojek is the most comfortable.